HUBUNGAN PENGUASAAN LAHAN DAN PENDAPATAN RUMAHTANGGA DI PEDESAAN (Kasus di Propinsi Jawa Tengah, Sumatera Barat dan Kalimantan Barat) - -, SUPRIYATI; -, SAPTANA; SUPRIYATNA, YANA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 3, No. 2 Juli 2003, 2012)
Historically correlation between landowner and land holding structure with household income structure in the rural area is linearity. Land owner or land holding structure inequality main factors to cause income structure inequality. In condition, there are the opportunity employ and economic activity to open up, why is the correlation between landowner and land holding structure with the income structure? This paper objective to study: (1) Land owner or land holding structure in the rural area; (2) Household income structure in the rural area; and (3) The correlation between landowner and land holding structure with the household income structure in the rural area. Location on this study to focused in the three district in three provincial exes. Klaten, central Java; Pasaman, West Sumatera; and Landak, West Kalimantan. The study to analyze by descriptive, gini index, and correlation analyze. In general, land owner and land holding size in Klaten, central Java less than West Sumatera and West Kalimantan. Gini index analysis relatively to indicate high equality, except in Pasaman, West Sumatera. Inequality on land holding lower than landowner in all location. Total income in Klaten, Central Java to range Rp. 6,77 - 6,97 million/years; Pasaman, West Sumatera to range Rp. 7,30 – Rp. 8,10 million/years; and in Landak, West Kalimantan to range Rp. 5,90 – 6,65 million/years. Analyze gini index for household income to indicate high inequality income structure rural area in Klaten. On the other hand, rural area in Pasaman, West Sumatera and Landak, West Kalimantan gini index result reflecting low inequality. There are deferent factors by location to cause inequality of landowner or land holding and household income structure, in Klaten rural area caused by high proportion income source from non-agriculture. On the other hand, in Pasaman and Landak rural area caused by level of technology adoption and kind of commodity planting by farmers. Statistically, correlation between landowner and land holding structure with household agriculture income is not significant. Correlation between total income with the landowner or land holding in Pasaman, West Java is significant, but in Klaten, Central Java and Landak, West Java is not significant.
Keywords: Land, Owner, Holding, Inequality, Income